Kandungan Antosianin dan Aktivitas Antioksidan Ubi Jalar Ungu Segar dan Produk Olahannya - Nida El Husna; Melly Novita; Syarifah Rohaya (agriTECH, 2013)
Purple fleshed sweet potato is a potential source of anthocyanins which is as an antioxidant, antimutagenic, and anticarcinogenic. Anthocyanins can be damaged by high temperatures. However, traditionally a number of processed sweet potato products involve heat treatment. This study aimed to assess the reduction of anthocyanins content in processed sweet potato products (flour, chips, sweet potato, steamed, boiled, and fried pieces) from two types of local purple fleshed sweet potato (light purple and dark purple), therefore it might provide useful information stages in order to maintain the content of anthocyanins. The experiment was arranged in a Randomized Complete Block Design (RCBD) of factorial arrangement treatments (two types of purple fleshed sweet potato, and five types of purple fleshed sweet potato processed products). The main analysis parameter are anthocyanins content and antioxidant activity. The anthocyanins content of dark purple fleshed sweet potato was 61.85 mg/100g, 17 times higher than light purple fleshed sweet potatoes 3.51 mg/100g. Dark purple fleshed sweet potatoes have antioxidant activity approximately 59.25%, greater than light purple fleshed sweet potatoes 56.64%. Decrease in anthocyanins content for processed products from both types of purple sweet potatoes showed the same trend. Purple sweet potato processed products that able to maintain fairly high the content of anthocyanins (the lowest rate of decline in anthocyanin levels) were obtained on a steamed sweet potato (34.14% for dark purple and 42.16% for light purple), while the highest reduction obtained on the product chips (95.21% for dark purple and 88.47% for light purple). Reduction of antioxidant activity showed a directly proportion of the decrease in anthocyanins content of processed products, with the exception of processed products chips.ABSTRAKUbi jalar ungu potensial sebagai sumber antosianin yang dapat berfungsi sebagai antioksidan, antimutagenik, dan antikarsinogenik. Antosianin dapat rusak akibat suhu tinggi (pemanasan) yang biasa digunakan dalam pembuatan sejumlah produk olahan ubi jalar. Penelitian ini bertujuan untuk mengkaji pengurangan/kehilangan antosianin pada produk olahan ubi jalar (tepung, keripik, ubi jalar kukus, rebus, dan goreng) dari dua jenis ubi jalar ungu lokal di Saree, Aceh Besar (ungu muda dan ungu pekat) sehingga dapat memberikan informasi proses pengolahan yang paling dapat mempertahankan kandungan antosianin. Penelitian disusun dengan Rancangan Acak Kelompok (RAK) faktorial 2 faktor, yaitu jenis ubi jalar ungu dan jenis produk olahan ubi jalar. Parameter analisis utama adalah kandungan antosianin dan aktivitas antioksidan. Ubi jalar ungu pekat mengandung antosianin 61,85 mg/100 g, 17 kali lebih tinggi dibandingkan dengan kandungan antosianin ubi jalar ungu muda 3,51 mg/100 g. Ubi jalar ungu pekat memiliki aktivitas antioksidan 59,25 %, lebih besar dibandingkan dengan ubi jalar ungu muda 56,64 %. Penurunan kandungan antosianin pada produk olahan dari kedua jenis ubi jalar menunjukkan kecenderungan yang sama. Produk olahan ubi jalar ungu yang paling mampu mempertahankan kandungan antosianin diperoleh pada ubi kukus yaitu 34,14 % (ungu pekat) dan 42,16 % (ungu muda), sedangkan tingkat penurunan tertinggi diperoleh pada produk keripik yaitu 95,21 % (ungu pekat) dan 88,47% (ungu muda). Penurunan aktivitas antioksidan juga berbanding lurus dengan penurunan kadar antosianin pada semua produk olahan, kecuali pada produk olahan keripik.